Landscape dynamics on the Ljubljana Moor - Mlekuž, Dimitrij (Documenta Praehistorica, 1999)
A geographical Information System (GIS) based dynamical model of streams migration was constructed in order to gain insight into the dynamics of the palaeo landscape. Model implication related to the settlement patterns and perception of the landscape by the mid-Holocene men and women dwelling in it are discussed.
Keywords: Ljubljankso barje; mezolitik; neolitik; eneolitik; archaeology; arheologija; geoarheologija; arheološke najdbe